Driving Value and Improving Efficiency: Digital Fuel Measurement as a Strategic Enabler in State-Owned Logistics — a Case Study of Limosin at Elnusa Petrofin - Dyah Ayu Sekar Melati; Nila Armelia Windasari (Green Publisher Indonesia, 2026)
This study examines the digital transformation of fuel logistics within Indonesian state-owned enterprises (SOEs), focusing on the implementation of LIMOSIN (Liquid Monitoring System) at Elnusa Petrofin. Despite global advances in IoT-enabled measurement systems, Indonesian fuel distribution continues to rely on manual dipstick measurement, handwritten logs, and fragmented reconciliation processes. Using a qualitative case study approach supported by the Technology Acceptance Model (TAM), Resource-Based View (RBV), VRIO, and Cost-Benefit Analysis (CBA), this research analyzed the operational, behavioral, and strategic implications of adopting digital fuel measurement systems. Findings reveal that LIMOSIN significantly improves accuracy, transparency, and traceability but faces adoption barriers due to low perceived ease of use, limited system integration, and institutional constraints typical of SOEs. Strategically, LIMOSIN positions Elnusa Petrofin toward greater client trust and differentiation in B2B logistics. The study contributes theoretical and managerial insights into digital adoption within emerging market SOEs and provides recommendations to strengthen readiness and strategic alignment.